Interferon regulatory factor 5 controls necrotic core formation in atherosclerotic lesions by impairing efferocytosis. - Seneviratne, C; Edsfeldt, A; Cole, J; Kassiteridi, C; Swart, M; Park, I; Green, P; Khoyratty, T; Saliba, D; Goddard, M; Sansom, S; Goncalves, I; et al. (American Heart Association, 2017)
Background Myeloid cells are central to atherosclerotic lesion development and vulnerable plaque formation. Impaired ability of arterial phagocytes to uptake apoptotic cells (efferocytosis), promotes lesion growth and establishment of a necrotic core. The transcription factor Interferon Regulatory Factor (IRF)-5 is an important modulator of myeloid function and programming. We sought to investigate whether IRF5 affects the formation and phenotype of atherosclerotic lesions Methods We investigated the role of IRF5 in atherosclerosis in two complementary models. First, atherosclerotic lesion development in hyperlipidemic apolipoprotein E-deficient (ApoE-/-10 ) mice and ApoE-/- mice with a genetic deletion of IRF5 (ApoE-/-Irf5-/-11 ) was compared then lesion development was assessed in a model of shear stress modulated vulnerable plaque formation. Results Both lesion size and necrotic core size were significantly reduced in ApoE-/-Irf5-/- mice compared to IRF5 competent ApoE-/- mice. Necrotic core size was also reduced in the model of shear stress modulated vulnerable plaque formation. A significant loss of CD11c+ macrophages was evident in ApoE-/-Irf5-/- mice in the aorta, draining lymph nodes and in bone marrow cell cultures, indicating that IRF5 maintains CD11c+ macrophages in atherosclerosis. Moreover, we revealed that the CD11c gene is a direct target of IRF5 in macrophages. In the absence of IRF5, CD11c- macrophages displayed a significant increase in expression of the efferocytosis regulating integrin-β3 and its ligand milk fat globule-EGF factor 8 protein (Mfge8) and enhanced efferocytosis in vitro and in situ. Conclusions IRF5 is detrimental in atherosclerosis by promoting the maintenance of pro-inflammatory CD11c+ macrophages within lesions and controlling the expansion of the necrotic core by impairing efferocytosis.